Modulator Induced Formation of a Neutral Framework Based on Trinuclear Cobalt(II) Clusters and Nitrilotribenzoic Acid: Synthesis, Magnetism, and Sorption Properties. Issue 23 (20th May 2021) - Akintola, Oluseun; Buchholz, Axel; Görls, Helmar; Plass, Winfried
Abstract: The solvothermal reaction of cobalt(II) chloride and 4, 4′, 4′′‐nitrilotribenzoic acid (H3 ntb) in dmf employing a modulator based approach leads to the formation of the neutral framework with the formula [Co9 (ntb)6 (solv)12 ] n (JUMP‐3). Different mono‐ and dicarboxylic acids such as benzoic, phthalic, isophthalic, and acetic acid could be used as appropriate modulator to trigger the reaction toward the formation of the neutral framework. X‐ray crystallography revealed a three‐dimensional network composed of linear trinuclear cobalt(II) units as metal nodes and the triarylamine linkers. The topological analysis showed that the framework adopts a 3, 6‐coordinated net with 3, 6T80 topology. Magnetic measurements performed in the temperature range of 2–300 K indicate antiferromagnetic interactions between the cobalt(II) ions within its linear trinuclear clusters. The N2 sorption properties were investigated and show the presence of micropores, which is consistent with the presence of the 1D channels in the crystal structure of JUMP‐3. Abstract : Inclusion of carboxylic acids as structure modulator in the reaction of nitrilotriacetic acid and cobalt(II) chloride resulted in the formation of a neutral MOF instead of the previously reported anionic frameworks. The magnetic properties of the constituent linear trinuclear cobalt(II) clusters are characterized by spin‐orbit and antiferromagnetic exchange interactions.